Realization of In‐Plane p–n Junctions with Continuous Lattice of a Homogeneous Material. Issue 30 (12th June 2018) - Huang, Xiaochun; Liu, Bing; Guan, Jiaqi; Miao, Guangyao; Lin, Zijian; An, Qichang; Zhu, Xuetao; Wang, Weihua; Guo, Jiandong
Abstract: Two‐dimensional (2D) in‐plane p–n junctions with a continuous interface have great potential in next‐generation devices. To date, the general fabrication strategies rely on lateral epitaxial growth of p‐ and n‐type 2D semiconductors. An in‐plane p–n junction is fabricated with homogeneous monolayer Te at the step edge on graphene/6H‐SiC(0001). Scanning tunneling spectroscopy reveals that Te on the terrace of trilayer graphene is p‐type, and it is n‐type on monolayer graphene. Atomic‐resolution images demonstrate the continuous lattice of the junction, and mappings of the electronic states visualize the type‐II band bending across the space‐charge region of 6.2 nm with a build‐in field of 4 × 10 5 V cm −1 . The reported strategy can be extended to other 2D semiconductors on patternable substrates for designed fabrication of in‐plane junctions. Abstract : An in‐plane p–n junction is fabricated by growing homogeneous monolayer tellurium across a step on graphene/6H‐SiC(0001). Scanning tunneling microscopy images demonstrate the continuous lattice of the junction without significant distortion, while mappings of the electronic states visualize type‐II band bending across the space‐charge region of 6.2 nm with a build‐in field of 4 × 10 5 V cm −1 .